Linoleic acid enhances prostaglandin signaling and IFNT expression in bovine trophoblast cells in vitro - Lucas de Oliveira Bezerra; Laura Chuba Machado Rolniche; Adriano Felipe Mendes; Amanda Guimarães da Silva; Isabella Rio Feltrin; Karine Galhego Morelli; Catarina Lazarevicius Prestes; Maria Eduarda Rocha Pinto; Mariângela Bueno Cordeiro Maldonado; Cecilia Constantino Rocha; Alan Ealy; Vitor Mercadante; et al. (Theriogenology, 2026)

MAELSTROM, a machine learning-based approach for stock assessment - Matteo Stefani; Simone Libralato; Cecilia Pinto; Tommaso Russo (Frontiers in Marine Science, 2026)
Managing the fishing industry is crucial to maintain a balance between the exploitation of marine resources and their natural ability to recover. To achieve such a goal, stock assessment models are built to combine commercial catches and population abundance time series. These approaches can often handle only single-species, losing the information regarding the ecological interactions affecting the dynamics of the species. Moreover, conventional stock assessment models are based on explicit deterministic equations, which can fail to represent the ecological interactions between the species and its environment. In this paper we present Maelstrom, a multispecies predictive model based on neural networks that can interpret fishery-dependent and -independent data to return a forecast of stock abundance considering variations in fishing effort. Although neural networks-based forecasting of ecological and fisheries time series is well established, we present a customizable Shiny tool in which a multi-species, age-structured framing is integrated and devised to be applied in real management frameworks. Namely, we set up five scenarios of increasing complexity in which three commercial species are considered. To assess the model's reliability, we conducted a benchmark test comparing Maelstrom to a routinely used stock assessment tool, the a4a model framework, using RMSE and MAE for validation. The results, besides showing a good degree of accuracy of Maelstrom to classical stock assessment models, endorse the potential of a multi-species approach even when working on shorter time-series. The Shiny application returns statistics, plots, and a report of all the operations conducted during the stock assessment.

A federal clean fuel standard (CFS) for the USA - Cato Sandford; Chris Malins; Maria Cecilia Pinto de Moura; Jeremy Martin (Energy Policy, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Unlocking the Potential of Marine Sidestreams in the Blue Economy: Lessons Learned from the EcoeFISHent Project on Fish Collagen - Lorenzo Dondero; Giulia De Negri Atanasio; Francesca Tardanico; Erica Lertora; Raffaella Boggia; Vittorio Capra; Agnese Cometto; Mattia Costamagna; Fi.L.S.E; Mirvana Feletti; Fulvio Garibaldi; Federica Grasso; et al. (Marine Biotechnology, 2025)
This review provides a general overview of collagen structure, biosynthesis, and biological properties, with a particular focus on marine collagen sources, especially fisheries discards and by-catches. Additionally, well-documented applications of collagen are presented, with special emphasis not only on its final use but also on the processes enabling sustainable and safe recovery from materials that would otherwise go to waste. Particular attention is given to the extraction process, highlighting key aspects essential for the industrialization of fish sidestreams, such as hygiene standards, adherence to good manufacturing practices, and ensuring minimal environmental impact. In this context, the EcoeFISHent projects have provided valuable insights, aiming to create replicable, systemic, and sustainable territorial clusters based on a multi-circular economy and industrial symbiosis. The main goal of this project is to increase the monetary income of certain categories, such as fishery and aquaculture activities, through the valorization of underutilized biomass.

FGF18 impairs blastocyst viability, DNA double-strand breaks and maternal recognition of pregnancy genes - André Lucio Fontana Goetten; Marcos Henrique Barreta; Yago Pinto da Silva; Kalyne Bertolin; Júlia Koch; Cecilia Constantino Rocha; Paulo Bayard Dias Gonçalves; Christopher Alan Price; Alfredo Quites Antoniazzi; Valerio Marques Portela (Theriogenology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Range expansion of the Atlantic fish Zenopsis conchifer (Lowe, 1852), family Zeidae, in the western Mediterranean Sea - CECILIA PINTO; GIOVANNI ROPPO VALENTE; NICOLA RASORE; EDOARDO OLMI; LUCA LANTERI; FULVIO GARIBALDI; CLAUDIO VIVA; ALESSANDRA NERI; ANDREA MASSARO; FRANCESCO De CARLO; ALESSANDRO LIGAS; PAOLO SARTOR (Mediterranean Marine Science, 2023)
Three specimens of Silver John dory, Zenopsis conchifer, (Lowe, 1852) were observed for the first time in the Ligurian Sea and northern Tyrrhenian Sea (western Mediterranean), one in 2020 and two in 2021. This is the fifth record (up to ten individuals) of Z. conchifer in the Mediterranean Sea, which occurred 11 years after the last observation in 2010 in the southern Tyrrhenian Sea. The present study reports the northernmost record of the species in the western Mediterranean Sea, indicating a potential range expansion of the distribution of this Atlantic species across the area. Morphometric, meristic and biological data of the three specimens are provided and compared with previous published records.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Mesoscale productivity fronts and local fishing opportunities in the European Seas - Jean‐Noël Druon; Didier Gascuel; Maurizio Gibin; Antonella Zanzi; Jean‐Marc Fromentin; Francesco Colloca; Pierre Hélaouët; Marta Coll; Alessandro Mannini; Joanna K Bluemel; Chiara Piroddi; Francois Bastardie; et al. (Fish and Fisheries, 2021)
This study evaluates the relationship between both commercial and scientific spatial fisheries data and a new satellite‐based estimate of potential fish production (Ocean Productivity available to Fish, OPFish) in the European Seas. To construct OPFish, we used productivity frontal features derived from chlorophyll‐ a horizontal gradients, which characterize 10%–20% of the global phytoplankton production that effectively fuels higher trophic levels. OPFish is relatively consistent with the spatial distribution of both pelagic and demersal fish landings and catches per unit of effort (LPUEs and CPUEs, respectively). An index of harvest relative to ocean productivity (H P index) is calculated by dividing these LPUEs or CPUEs with OPFish. The H P index reflects the intensity of fishing by gear type with regard to local fish production. Low H P levels indicate lower LPUEs or CPUEs than expected from oceanic production, suggesting over‐exploitation, while high H P levels imply more sustainable fishing. H P allows comparing the production‐dependent suitability of local fishing intensities. Our results from bottom trawl data highlight that over‐exploitation of demersal species from the shelves is twice as high in the Mediterranean Sea than in the North‐East Atlantic. The estimate of H P index by dominant pelagic and demersal gears suggests that midwater and bottom otter trawls are associated with the lowest and highest overfishing, respectively. The contrasts of fishing intensity at local scales captured by the H P index suggest that accounting for the local potential fish production can promote fisheries sustainability in the context of ecosystem‐based fisheries management as required by international marine policies.

Purification of protein from Arthrospira platensis using aqueous two-phase system associate with membrane separation process and evaluation of functional properties - Anne Luize Lupatini Menegotto; Ilizandra Aparecida Fernandes; Danieli Bucior; Bianca Pinto Balestieri; Luciane Maria Colla; Cecilia Abirached; Elton Franceschi; Juliana Steffens; Eunice Valduga (Journal of Applied Phycology, 2021)

“The Elephant in the Room”: Exploring Natural Mortality Uncertainty in Statistical Catch at Age Models - Alessandro Mannini; Cecilia Pinto; Christoph Konrad; Paraskevas Vasilakopoulos; Henning Winker (Frontiers in Marine Science, 2020)
The natural mortality rate (M) of a fish stock is typically highly influential on the outcome of age-structured stock assessment models, but at the same time extremely difficult to estimate. In data-limited stock assessments, M usually relies on a range of empirically or theoretically derived M estimates, which can vary vastly. This article aims at evaluating the impact of this variability in M using seven Mediterranean stocks as case studies of statistical catch-at-age assessments for information-limited fisheries. The two main bodies carrying out stock assessments in the Mediterranean and Black Seas are European Union’s Scientific Technical Economic Committee for Fisheries (STECF) and Food and Agriculture Organization’s General Fisheries Commission for the Mediterranean (GFCM). Current advice in terms of fishing mortality levels is based on a single “best” M assumption which is agreed by stock assessment expert working groups, but uncertainty about M is not taken into consideration. Our results demonstrate that not accounting for the uncertainty surrounding M during the assessment process can lead to strong underestimation or overestimation of fishing mortality, potentially biasing the management process. We recommend carrying out relevant sensitivity analyses to improve stock assessment and fisheries management in data-limited areas such as the Mediterranean basin.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Selectivity metrics for fisheries management and advice - Paraskevas Vasilakopoulos; Ernesto Jardim; Christoph Konrad; Dominic Rihan; Alessandro Mannini; Cecilia Pinto; John Casey; Iago Mosqueira; Finbarr G. O’Neill (Fish and Fisheries, 2020)
Fisheries management typically aims at controlling exploitation rate (e.g., Fbar) to ensure sustainable levels of stock size in accordance with established reference points (e.g., F MSY , B MSY ). Population selectivity (“selectivity” hereafter), that is the distribution of fishing mortality over the different demographic components of an exploited fish stock, is also important because it affects both Maximum Sustainable Yield (MSY) and F MSY , as well as stock resilience to overfishing. The development of an appropriate metric could make selectivity operational as an additional lever for fisheries managers to achieve desirable outcomes. Additionally, such a selectivity metric could inform managers on the uptake by fleets and effects on stocks of various technical measures. Here, we introduce three criteria for selectivity metrics: (a) sensitivity to selectivity changes, (b) robustness to recruitment variability and (c) robustness to changes in Fbar. Subsequently, we test a range of different selectivity metrics against these three criteria to identify the optimal metric. First, we simulate changes in selectivity, recruitment and Fbar on a virtual fish stock to study the metrics under controlled conditions. We then apply two shortlisted selectivity metrics to six European fish stocks with a known history of technical measures to explore the metrics’ response in real‐world situations. This process identified the ratio of F of the first recruited age–class to Fbar (Frec/Fbar) as an informative selectivity metric for fisheries management and advice.

Recent cyanobacteria abundance in a large sub-tropical reservoir inferred from analysis of sediment cores - Daniela Gangi; María Sofía Plastani; Cecilia Laprida; Andrea Lami; Nathalie Dubois; Facundo Bordet; Claudia Gogorza; Diego Frau; Paula de Tezanos Pinto (Journal of Paleolimnology, 2020)

Molecular and morphological differentiation among Torrent Duck ( Merganetta armata ) populations in the Andes - Natalia Gutiérrez‐Pinto; Kevin G. McCracken; Pablo Tubaro; Cecilia Kopuchian; Andrea Astie; Carlos Daniel Cadena (Zoologica Scripta, 2019)
Birds living in riverine environments may show weak population structure because high dispersal abilities required to track habitat dynamics can result in gene flow over broad spatial scales. Alternatively, the configuration of river networks may result in restricted dispersal within river courses or basins, leading to high genetic structure. Although several bird species are riverine specialists in the Andes, no study has extensively evaluated the population genetic structure of any of them. We examined evidence from genetic and morphological data to address questions about the biogeography and taxonomy of the Torrent Duck ( Merganetta armata ), a riverine specialist bird with a broad distribution in Andean riverine habitats which certainly comprises different subspecies and may comprise more than one species. We found deep subdivisions of Torrent Duck populations from the northern, central and southern portions of the Andes. These lineages, which partly coincide with subspecies described based on plumage variation and body size, do not share mtDNA haplotypes, have private nuclear alleles and exhibit marked differences in morphometric traits. Some geographic barriers presumably restricting gene flow between groups partially coincide with those associated with major genetic breaks in forest species with similar distributions along the Andes, suggesting that bird assemblages including species occupying different habitats were likely affected by common biogeographical events. The three groups of Torrent Ducks may be considered different species under some species definitions and are distinct evolutionary lineages to be conserved and managed separately.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Setting population targets for mammals using body mass as a predictor of population persistence - Jelle P. Hilbers; Luca Santini; Piero Visconti; Aafke M. Schipper; Cecilia Pinto; Carlo Rondinini; Mark A.J. Huijbregts (Conservation Biology, 2017)
Conservation planning and biodiversity assessments need quantitative targets to optimize planning options and assess the adequacy of current species protection. However, targets aiming at persistence require population‐specific data, which limit their use in favor of fixed and nonspecific targets, likely leading to unequal distribution of conservation efforts among species. We devised a method to derive equitable population targets; that is, quantitative targets of population size that ensure equal probabilities of persistence across a set of species and that can be easily inferred from species‐specific traits. In our method, we used models of population dynamics across a range of life‐history traits related to species’ body mass to estimate minimum viable population targets. We applied our method to a range of body masses of mammals, from 2 g to 3825 kg. The minimum viable population targets decreased asymptotically with increasing body mass and were on the same order of magnitude as minimum viable population estimates from species‐ and context‐specific studies. Our approach provides a compromise between pragmatic, nonspecific population targets and detailed context‐specific estimates of population viability for which only limited data are available. It enables a first estimation of species‐specific population targets based on a readily available trait and thus allows setting equitable targets for population persistence in large‐scale and multispecies conservation assessments and planning.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Bromeliad growth and stoichiometry: responses to atmospheric nutrient supply in fog-dependent ecosystems of the hyper-arid Atacama Desert, Chile - Angélica L. González; José Miguel Fariña; Raquel Pinto; Cecilia Pérez; Kathleen C. Weathers; Juan J. Armesto; Pablo A. Marquet (Oecologia, 2011)